Long-term sequalae of pelvic inflammatory diseases - Pavel Sitnik; Victoria Levkovska (Kazimierz Wielki University, 2016)
Sitnik P., Levkovska V. Long-term sequalae of pelvic inflammatory diseases. Journal of Education, Health and Sport. 2016;6(10):40-43. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159796 http://ojs.ukw.edu.pl/index.php/johs/article/view/3925       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 08.10.2016.       Long-term sequalae of pelvic inflammatory diseases   Sitnik P., Levkovska V.   Odessa National Medical University, Odessa, Ukraine       SUMMARY The aim of the study was to assess the long-term sequalae of pelvic inflammatory diseases amongst females living in the Southern Ukraine region. The most common sequela of PID was chronic pelvic pain (24.4% in 12 months after treatment, 69.2% - in 24 months, 80.0% - in 36 months). No cases of eutopic pregnancies were recorded during all follow-up period but 3 (4.0%) cased of ectopic pregnancies were recorded. 4 patients experienced recurrent PID episodes during this period. The long term sequalae of PID were associated with severe disease, delay in treatment and recurrent infection. Thus early diagnosis and intervention in the cases of acute PID are drastically  important for the prevention of further long-term sequalae. When considering preventive strategies, prevention of recurrent PID is an important goal as it has been shown that the sequalae of PID could be worsened with repeated episodes of PID.   Key words: pelvic inflammatory disease, sequalae, reproductive health